Mengungkap Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus KPP Pratama Kepanjen) - Nirwana, Lintang Fajar; Sudaryanti, Dwiyani; Junaidi, Junaidi (Universitas Islam Malang, 2024)
Taxes are one of the main sources for generating revenue. They represent the largest source of income in the State Budget (APBN). The revenue obtained from taxation is used to fund various government expenditures aimed at improving the welfare of the people. The purpose of this research is to examine the impact of the Voluntary Disclosure Program (PPS), tax sanctions, and taxpayer awareness on individual taxpayer. Sampling in this study was conducted using the Slovin formula. This research employs a quantitative method using accidental sampling with a sample of 100 individual taxpayers in the Kepanjen district who are registered at the Kepanjen Primary Tax Office (KPP Pratama Kepanjen). This research indicates that the Voluntary Disclosure Program, Tax Sanctions, and Taxpayer Awareness collectively have a simultaneous impact on Individual Taxpayer Compliance at the Kepanjen Primary Tax Office (KPP Pratama Kepanjen). Through this research, it is hoped that taxpayers will be able to fulfill their rights and obligations in accordance with the applicable tax procedures and regulations. Additionally, the research aims to enhance knowledge of taxation and improve tax complianceKeywords: Voluntary disclosure program, tax sanctions, tax awareness, taxpayer compliance.